Horizontes e dimensões do atual fenômeno migratório internacional - Federica Bertagna; João Carlos Tedesco (Ciências Sociais Unisinos)
The phenomenon of the international migrations reveals an expressive dynamics of the current world mainly in its economic, cultural and political scopes. The study analyzes some of these aspects based on the reality observed in Italy. The intention is to demonstrate aspects of its dynamics, implications and socio-ethnic performance.